Experience of Treating COVID-19 With Remdesivir and Convalescent Plasma in a Resource-Limited Setting: A Prospective, Observational Study. (21st August 2021) - Koirala, Janak; Gyanwali, Pradip; Gerzoff, Robert B; Bhattarai, Saroj; Nepal, Bipin; Manandhar, Rekha; Jha, Runa; Sharma, Sanjib; Sharma, Yuba Raj; Bastola, Anup; Murphy, Holly; Acharya, Subhash; et al.
Abstract: Background: Convalescent plasma therapy (CPT) and remdesivir (REM) have been approved for investigational use to treat coronavirus disease 2019 (COVID-19) in Nepal. Methods: In this prospective, multicentered study, we evaluated the safety and outcomes of treatment with CPT and/or REM in 1315 hospitalized COVID-19 patients over 18 years in 31 hospitals across Nepal. REM was administered to patients with moderate, severe, or life-threatening infection. CPT was administered to patients with severe to life-threatening infections who were at high risk for progression or clinical worsening despite REM. Clinical findings and outcomes were recorded until discharge or death. Results: Patients were classified as having moderate (24.2%), severe (64%), or life-threatening (11.7%) COVID-19 infection. The majority of CPT and CPT + REM recipients had severe to life-threatening infections (CPT 98.3%; CPT + REM 92.1%) and were admitted to the intensive care unit (ICU; CPT 91.8%; CPT + REM 94.6%) compared with those who received REM alone (73.3% and 57.5%, respectively). Of 1083 patients with reported outcomes, 78.4% were discharged and 21.6% died. The discharge rate was 84% for REM (n = 910), 39% for CPT (n = 59), and 54.4% for CPT + REM (n = 114) recipients. In a logistic model comparing death vs discharge and adjusted for age, gender, steroid use, and severity, the predicted margin for discharge was higher for recipients of remdesivir alone (0.82; 95% CI, 0.79–0.84) compared with CPT (0.58; 95% CI, 0.47–0.70) and CPT + REM (0.67; 95% CI, 0.60–0.74) recipients. Adverse events of remdesivir and CPT were reported in <5% of patients. Conclusions: This study demonstrates a safe rollout of CPT and REM in a resource-limited setting. Remdesivir recipients had less severe infection and better outcomes. ClinicalTrials.gov identifier. NCT04570982.